Analysis of the Effectiveness of Promotion of Food Products in Indonesian Marketplace - Ridha Rizki Novanda (International journal of technology and education research, 2023)
The development of marketplace sheds light on how Indonesia's business climate has altered in reaction to the growth of the internet. A marketplace firm that uses the C2C (consumer to consumer) business model, a subset of marketplace firms that just serve as a platform to connect consumers and sellers. Through the advertising, it will be discovered that businesses can introduce new food items that will entice customers to engage in food product purchasing activities. Therefore the purpose of this study is to analyze the effectiveness of the promotion of food products through the marketplace (tokopedia) in Indonesia. The major data gathering method, used in the first quarter of 2023, is the methodology employed in this study. Users of the marketplace were given access to an electronic form for data gathering. Tokopedia users used as respondents are 100 people and analyzed the results of the questionnaire collection based on applicable theories. The method used to determine the effectiveness of a promotional program, the dimensions used are emphaty (empathy), persuasion (persuasion), impact (impact), and communication (communication) or epic model. Based on the calculations made using the epic model, a value of 3.82 was determined, indicating that the Tokopedia food goods have been effectively promoted. The promotion program for food products that Tokopedia has implemented is successful for the four epic dimensions of Tokopedia, according to the average value of user perceptions on the site regarding sales promotion programs to the purchasing behavior of the four dimensions of empathy, persuasion, impact, and communication.